Resonance States of Hadronic Three-Body Ions: Stabilization Method (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
Bound and resonance states of symmetric three-body exotic \(pXX\) negative atomic ions \((X=μ^{-}, π^{-}, K^{-})\) as well as exotic \(ppX\) positive molecular ions for total angular momentum \(J=0\), are studied in details under the framework of Stabilization method. The resonance states under consideration lie below \(N=2\) ionization threshold of the corresponding \(pX\) atom. The wave-function is expanded in correlated multi-exponent Hylleraas type basis set for explicit incorporation of \(p\)-\(p\), \(μ\)-\(μ\), \(π\)-\(π\) or \(K\)-\(K\) correlations. The methodology has been tested by estimating the parameters of the resonance states of \((pμμ)^{-}\), \((ppμ)^{+}\), \((pππ)^{-}\) and \((ppπ)^{+}\) and comparing with the results existing in the literature. The interparticle interactions for all the systems under consideration are purely Coulombic.
Keywords: Three-body systems; Stabilization method; Hylleraas coordinate; Resonance state; Correlation